Coupled model biases breed spurious low-frequency variability in the tropical Pacific Ocean - Samanta, Dhrubajyoti (2018)
Coupled general circulation model (GCM) biases in the tropical Pacific are substantial, including a westward extended cold sea surface temperature (SST) bias linked to El Niño–Southern Oscillation (ENSO). Investigation of internal climate variability at centennial timescales using multicentury control integrations of 27 GCMs suggests that a Pacific Centennial Oscillation emerges in GCMs with too strong ENSO variability in the equatorial Pacific, including westward extended SST variability. Using a stochastic model of climate variability (Hasselmann type), we diagnose such centennial SST variance in the western equatorial Pacific. The consistency of a simple stochastic model with complex GCMs suggests that a previously defined Pacific Centennial Oscillation may be driven by biases in high‐frequency ENSO forcing in the western equatorial Pacific. A cautious evaluation of long‐term trends in the tropical Pacific from GCMs is necessary because significant trends in historical and future simulations are possible consequences of biases in simulated internal variability alone.